1999
DOI: 10.1016/s0014-5793(99)01595-1
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum vesicles embedded in agarose gel exhibit propagating calcium waves

Abstract: In different cell types, activation of signal transduction pathways leads to the generation of calcium oscillations and/ or waves. Due to this important impact for cellular function, calcium waves are the subject of intensive investigations. To study interactions of cell organelles with no influence of the cell membrane, sarcoplasmic reticulum (SR) vesicles and wellcoupled mitochondria were reconstituted. For the first time, we demonstrate the generation and propagation of calcium waves in a suspension of sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…For example, mitochondrial Ca 2+ retention may be crucially involved within the redistribution of [Ca 2+ ] cyt , to avoid harmful effects while accumulating in very high concentrations in the close proximity of mitochondria and Ca 2+ channels of the cell membrane or EPR/SR [ 109 111 ]. In addition, mitochondrial Ca 2+ cycling may be vital for governing the cytosolic Ca 2+ -waves [ 86 , 112 , 113 ]. To address the latter function of mitochondria within the the intracellular Ca 2+ homeostasis, we assessed the spontaneous Ca 2+ waves by confocal scanning fluorescence microscopy, using fluo-3 as a Ca 2+ sensor in a cell free system (an agarose gel supplemented with isolated SR vesicles, cardiac mitochondria, CK-based ATP regenerating system, and 5 mM ATP) [ 86 ].…”
Section: The Cellular Energetic Depression and Mitochondrial Cell Deamentioning
confidence: 99%
“…For example, mitochondrial Ca 2+ retention may be crucially involved within the redistribution of [Ca 2+ ] cyt , to avoid harmful effects while accumulating in very high concentrations in the close proximity of mitochondria and Ca 2+ channels of the cell membrane or EPR/SR [ 109 111 ]. In addition, mitochondrial Ca 2+ cycling may be vital for governing the cytosolic Ca 2+ -waves [ 86 , 112 , 113 ]. To address the latter function of mitochondria within the the intracellular Ca 2+ homeostasis, we assessed the spontaneous Ca 2+ waves by confocal scanning fluorescence microscopy, using fluo-3 as a Ca 2+ sensor in a cell free system (an agarose gel supplemented with isolated SR vesicles, cardiac mitochondria, CK-based ATP regenerating system, and 5 mM ATP) [ 86 ].…”
Section: The Cellular Energetic Depression and Mitochondrial Cell Deamentioning
confidence: 99%
“…A functional coupling between voltage-dependent Ca 2+ channels in the plasma membrane, Ca 2+ stores of the endoplasmic reticulum and mitochondria has also been demonstrated for excitable cells [25]. Mitochondria are also proposed to be involved in oscillations of the intracellular free Ca 2+ concentration [32] and Ca 2+ wave propagation [37]. For insulin-secreting INS-1 cells it has been shown that glucose does not only increase the cytosolic but also the intramitochondrial free Ca 2+ concentration [13].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical means for forming oscillatory standing and traveling wave patterns over various biocellular network topologies have been successfully demonstrated before [3,4,7,8,10,42,43]. We presented a unified methodology to build biocellular networks of increasing complexity in a systematic fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Identical biochemical content and morphology for the participating entities in such biological systems precludes global control by a single member as the mechanism of coordination. Instead, local molecule-tomolecule [2], organelle-to-organelle [3], cell-to-cell [4,5] or organism-to-organism [6] interactions lead to spatio-temporal pattern formation. In multicellular domains, these interactions can be surprisingly simple such as the receptor-ligand binding involved in Delta-Notch signaling pathway [7] or even simpler as in diffusion of inositol (1,4,5)-triphosphate (IP 3 ) and Ca 2+ participating in intracellular and intercellular Ca 2+ waves [8].…”
Section: Introductionmentioning
confidence: 99%